Sensorless point-to-point control for a musculoskeletal tendon-driven manipulator: analysis of a two-DOF planar system with six tendons. (18th August 2017) - Kino, H.; Ochi, H.; Matsutani, Y.; Tahara, K.
Abstract : Tendon-driven robot utilizes only tensile force (i.e. tension) for motion generation. Therefore, a redundant actuation is characteristically necessary, and then it yields the internal force among tendons. Given the internal force for balance at a desired posture, the musculoskeletal tendon-driven manipulator has the inherent possibility of point-to-point position control without any sensory feedback. However, the motion convergence is strongly governed by the arrangement of tendons.This study analyzes the mathematical conditions of convergence for this sensorless position control by use of a Lyapunov function. Subsequently, targeting the two-link musculoskeletal structure with six tendons, the sufficient conditions for the convergence at desired posture are further defined by employing an approximation of the tendon-length based on a Taylor expansion. Finally, the convergent conditions are verified through simulation and validated via experimental results. Graphical Abstract: